Failure and Equality in Functional Logic Programming - López-Fraguas, F.J.; Sánchez-Hernández, J. (Electronic notes in theoretical computer science, 2003)
Constructive failure has been proposed recently as a programming construct useful for functional logic programming, playing a role similar to that of constructive negation in logic programming. On the other hand, almost any functional logic program requires the use of some kind of equality test between expressions. We face in this work in a rigorous way the interaction of failure and equality (even for non-ground expressions), which is a non trivial issue, requiring in particular the use of disequality conditions at the level of the operational mechanism of constructive failure. As an interesting side product, we develop a novel treatment of equality and disequality in functional logic programming, by giving them a functional status, which is better suited for practice than previous proposals.